Femtosecond laser inscription of Bragg and complex gratings in low-Loss polymer and silica optical fibers - Kalli, Kyriacos; Lacraz, Amédéé; Michael, Polis (My University, 2015)
The development of Bragg and superstructure gratings in coated glass and low-loss polymer optical fibers, using a femtosecond laser, is reported. The femtosecond laser operates in the green, which offers greater inscription efficiency.
Keywords: Bragg; Femtosecond laser